Anisotropic etching of graphite and graphene in a remote hydrogen plasma - D. Hug (Nature Portfolio, 2017)
Nanofabrication: remote etching of graphene on hBN is highly anisotropic Etching of graphite with hydrogen plasma gives rise to two distinct etching regimes, governed by the degree of direct plasma exposure. A team led by D. M. Zumbühl at the University of Basel investigated the interplay between graphite exposure to pure hydrogen plasma and the resulting etching features. When the sample surface is in direct contact with the plasma, a defect-rich etching regime occurs, resulting in the formation of etch pits with variable size. However, when graphite is away from the plasma source, a remote anisotropic etching takes place, giving rise to regular hexagons originating from localized defects and edges. In the latter regime, the authors found that in the case of graphene, isotropic etching is obtained using SiO2 as substrate, whereas highly anisotropic etching occurs when graphene is placed on hBN.